A new commentary on the Old English 'Prose Solomon and Saturn' and 'Adrian and Ritheus' dialogues - Wright, Charles Darwin 1954-; Hall, Thomas N.; Hill, Thomas D. 1940- (Brepols, 2024)
"Who was not born, was buried in his mother?s womb, and was baptized after death? Who first spoke with a dog? Why don?t stones bear fruit? Who first said the word ?God?? Why is the sea salty? Who built the first monastery? Who was the first doctor? How many species of fish are there? What is the heaviest thing to bear on earth? What creatures are sometimes male and sometimes female? The Old English dialogues 'The Prose Solomon and Saturn' and 'Adrian and Ritheus', critically edited in 1982 by J. E. Cross and Thomas D. Hill, provide the answers to a trove of curious medieval "wisdom questions" such as these, drawing on a remarkable range of biblical, apocryphal, patristic, and encyclopaedic lore.00This volume (which reprints the texts and translations of the two dialogues from Cross and Hill?s edition) both updates and massively supplements the commentary by Cross and Hill, contributing extensive new sources and analogues (many from unpublished medieval Latin question-and-answer texts) and comprehensively reviews the secondary scholarship on the ancient and medieval texts and traditions that inform these Old English sapiential dialogues. It also provides an extended survey of the late antique and early medieval genres of ?curiosity? and ?wisdom? dialogues and florilegia, including their dissemination and influence as well as their social and educational functions."
Keywords: Adrian and Ritheus; Salomon and Saturn; Kommentar